FACTORS EXPLAINING BUSINESS DEVELOPMENT ON MSME: A THEORETICAL APPROACH - Bryandhito, Irsyad; Suparno; Lestari, Fitra Dila (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
The research aims to develop theoretical modeling of business development in MSME. Various factors that influence business development are analyzed and identified as the main factors in developing MSME businesses, namely economic learning experience and creativity. The research strategy utilized is subjective with writing considers, proposition analyzing speculations and past analysts and deciding the most variables as indicators of business development. Shows that creativity is a mediator of economic learning experiences on business development. Recommendations for other researchers are to test the effect of economic learning experiences on the development of MSME businesses through creativity mediation, either quantitative test, or developed in aspects of other.